1994
DOI: 10.1164/ajrccm.149.2.7905767
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-induced lung injury in the guinea pig proceeds through CD18-independent mechanisms.

Abstract: The pathogenesis of pulmonary oxygen toxicity is postulated to be related in part to neutrophil-mediated injury. This study examined the effect of a monoclonal antibody directed against the CD11a,b,c/CD18 glycoprotein complex (beta 2 leukocyte integrins) on oxygen-induced lung injury. M8, a monoclonal antibody that binds to the beta chain of the guinea pig leukocyte integrins that facilitate neutrophil adherence to vascular endothelium, was injected into adult guinea pigs prior to and during exposure to > 98% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 25 publications
2
12
0
1
Order By: Relevance
“…However, the relative importance of these CAMs to sequential changes in cellular trafficking during prolonged O 2 exposure is still unknown. It has been suggested that PMN influx during hyperoxic exposure occurs through a predominantly CD11/ CD18-independent pathway (19,26). Keeney et al (26), using an MAb directed against the CD18 complex in adult guinea pigs, found no change in neutrophil influx or lung injury after 72 h of hyperoxia, suggesting a predominantly CD18-independent pathway for emigration.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relative importance of these CAMs to sequential changes in cellular trafficking during prolonged O 2 exposure is still unknown. It has been suggested that PMN influx during hyperoxic exposure occurs through a predominantly CD11/ CD18-independent pathway (19,26). Keeney et al (26), using an MAb directed against the CD18 complex in adult guinea pigs, found no change in neutrophil influx or lung injury after 72 h of hyperoxia, suggesting a predominantly CD18-independent pathway for emigration.…”
Section: Discussionmentioning
confidence: 99%
“…7 In contrast, hyperoxia can induce ALI in animal models that lack leukocytes. [28][29][30][31] This dissociation demonstrates that HALI-induced tissue injury cannot be attributed solely to local tissue inflammation.…”
Section: Cell Death Mechanisms In Halimentioning
confidence: 95%
“…Doerschuk et al (54) demonstrated a number of years ago that this process can occur through at least two distinct pathways. One pathway reguires ␤ 2 -integrins, whereas the other does not, and the distinction depends on the stimulus (54,96,126,137,180,185,203,205,234). There is also evidence from studies in the peritoneal cavity that macrophages are essential for production of a stimulus that elicits ␤ 2 -integrin-independent neutrophil emigration (173).…”
Section: Introductionmentioning
confidence: 99%